Yemoja : gender, sexuality, and creativity in the Latina/o and Afro-Atlantic diasporas - Otero, Solimar; Falola, Toyin (State University of New York Press, 2013)
This book bridges theory, art, and practice to discuss emerging issues in transnational religious movements in Latina/o and African diasporas.